What path should I take? A qualitative study exploring the process of widowhood for older women - Coochise, Jodi L., author; Vacha-Haase, Tammi, advisor; Rickard, Kathryn, committee member; Swaim, Randall, committee member; Matheson, Jennifer, committee member (Colorado State University. Libraries, 2014)
The present qualitative study explored the process older adult women experience as they navigate their course through widowhood. Interviews were conducted with 10 women over the age of 55 to investigate what factors went in to their decisions regarding coping with the loss of their spouse. Findings suggest that women looked to others for guidance and advice in navigating multiple aspects of their experience. They turned to peers with experience of a similar loss, listened to their internal voice of what was a good fit, and focused on taking one day at a time. Messages from others, the perceived expectations of others, and their own internal expectations also shaped their widowhood experience. Ultimately, they had to determine what coping strategies were a good match and provided some relief from their distress. The findings suggest that widowed women may benefit from exploring the input received from others, increasing awareness around the messages received from family regarding loss and encouragement to utilize their internal voice as a guide for creating their own unique experience of grief.
Keywords: grief; widowhood; widow; spousal loss